Validation of a one-step reverse transcription PCR detection method for Tobamovirus maculatessellati, in tomato (Solanum lycopersicum L.) and pepper (Capsicum annuum L.) - Chellappan Padmanabhan; Andrea Gilliard; Kai-Shu Ling; Yazmín Rivera (Frontiers in Plant Science)
The solanaceous-infecting tobamoviruses are closely related and hence it can be challenging to detect them using serological or molecular methods, particularly when present in a mixed infection. Tomato mottle mosaic virus (ToMMV) is a newly identified tobamovirus that poses serious risk to tomato (Solanum lycopersicum L.) and pepper (Capsicum annuum L.) production worldwide. Species-specific identification is crucial to prevent the entry and establishment of plant pathogens and protect the billion-dollar tomato industry. In this study, we report the validation of a previously described reverse transcription polymerase chain reaction (RT-PCR) assay that amplifies a 289 bp fragment of the coat protein coding region of ToMMV genome. This assay has 100% specificity for ToMMV. Inclusivity tests were performed against a diverse collection of six ToMMV isolates in North America. Exclusivity tests showed no cross reaction with eleven non-target viruses and seven viroids commonly found on tomato and pepper host plants. The detection limit of the one-step RT-PCR was determined to be at 10-5 (or 0.25pg/μl) dilution in plant samples, with its amplicon sequence confirmed by Sanger sequencing. The RT-PCR can detect ToMMV consistently on contaminated seed or leaf tissues. This validated assay could serve as a standard method for detecting ToMMV in seed health testing and for plant disease diagnosis, thus to prevent inadvertent introduction and spread of this emerging and economically important tobamovirus in tomato and pepper fields.